Understanding information transformation anticipate the extraordinary. - Linthicum, David S.
The transformation layer is the "Rosetta stone" of the system. It understands the format of all information being transmitted among the applications and translates that information on the fly, restructuring data from one message so that it makes sense to the receiving application or applications. It provides a common dictionary that contains information on how each application communicates outside itself (application externalization), as well as which bits of information have meaning to which applications.